Emerging trends and research hotspots of non-invasive brain stimulation for stroke: a bibliometric and visualization study - Li, Zhengyu; Zhao, Xi; Xie, Siyu; Shi, Wenying; Zhang, Wei (Frontiers in Neurology, 2025)
ObjectivesWith the advent of an aging population society, the morbidity and mortality rates of stroke are on the rise. Most surviving patients are often accompanied by a series of sequelae, which seriously affect patients’ social function and physical and mental health. The application of non-invasive brain stimulation (NIBS) in neurorehabilitation has attracted widespread attention. This study aims to explore the key theme and future direction of the research in this field.MethodsArticles and reviews related to NIBS for stroke from January 1985 to September 2024 were identified from the Web of Science Core Collection database. The CiteSpace, VOSviewer software, and Charticulator website were used to visualize and analyze the publications, countries, institutions, authors, journals, keywords, cited references, subject categories, and funding agencies from various angles.ResultsA total of 4,453 papers were included in this study, with the United States publishing the most, followed by China. The most outstanding author was Fregni F from Harvard Medical School. Frontiers in Neurology had the highest number of publications. Plasticity and excitability represent two particularly major themes, and connectivity is the keyword of the research frontier in recent years.ConclusionNIBS shows considerable potential and broad development space in stroke rehabilitation. This study analyses the research hotspots and emerging trends in this field, thereby providing a framework for deeper research and contributing to the vigorous development of NIBS for stroke.